Decoding canine parvovirus: biomarkers for diagnosis and advances in vaccine development to address emerging challenges - Li, Hao; Li, Shengnan; Pan, Ye; Shi, Qiumei (Frontiers in Veterinary Science, 2025)
Canine parvovirus (CPV) enteritis is a highly contagious disease caused by CPV, primarily affecting canids and posing a severe threat to their health. Prevention of CPV infection relies mainly on attenuated live vaccines, subunit vaccines, and inactivated vaccines, all of which can induce protective immunity. However, the incomplete protective efficacy provided by some vaccines and fatalities in dogs due to immunization failure have significantly impacted the dog-breeding industry. Early diagnosis is crucial for timely treatment, but traditional detection methods like hemagglutination inhibition tests often lead to misdiagnosis, delaying therapy. In recent years, with in-depth research, novel diagnostic techniques and advanced vaccines have been continuously developed, achieving notable progress. Against this backdrop, this review summarizes the advancements in CPV vaccines based on domestic and international studies on CPV biomarkers and vaccination strategies. Specifically, the etiological characteristics of CPV exhibit dynamic evolutionary trends. Key amino acid mutations in the VP2 capsid protein (e.g., D426E) drive viral antigenic drift, giving rise to variants such as CPV-2a, 2b, and 2c. CPV-2c has become the predominant strain in Europe and South America, with conformational changes in its antigenic epitopes reducing neutralizing antibody titers induced by traditional vaccines by 4–8 folds. In terms of biomarkers, CPV infection triggers multi-systemic changes, including blood components (e.g., hematocrit, white blood cell count, platelet count), biochemical indicators (sodium/chloride electrolytes, hepatic/renal function markers), C-reactive protein (CRP), intestinal markers (I-FABP, TFF-3), and cardiac markers (cTnI, CK-MB). These markers are used to assess infection status, disease severity, and prognosis (e.g., CRP > 92.4 mg/L predicts mortality with 91% sensitivity). In vaccine development, attenuated live vaccines remain effective for preventing CPV enteritis but face challenges like maternal antibody interference and reduced efficacy caused by viral mutation. Inactivated vaccines offer high safety but low immunogenicity, requiring multiple vaccine administrations. DNA vaccines and subunit vaccines (e.g., virus-like particles self-assembled by VP2 protein) show promising prospects, with novel CPV-2c vaccines overcoming maternal antibody interference in puppies. However, the high mutation rate of CPV (0.0045 substitutions/site/year for VP2 gene) delays the updating of traditional vaccine strain updating, necessitating accelerated development of vaccines targeting prevalent strains (e.g., CPV-2c). Future research should focus on viral mutation monitoring, precision diagnostic technology, and strain-matched vaccine development to enhance CPV control efficiency.